OP0147 Intrinsic Cartilage Repair by Joint Distraction is Triggered by a Regenerative Transcriptional Response. (9th June 2015) - Mastbergen, S.C.; Miranda, A.; Coeleveld, K.; Meij, B.P.; van Roermund, P.M.; Tryfonidou, M.; Lafeber, F.P.
Abstract : Background: Joint distraction provides long-term improvement of pain and function, accompanied by intrinsic cartilage repair evaluated indirectly by imaging and biochemical markers in humans with knee osteoarthritis (OA) (Wiegant et al, 2013). Moreover, joint distraction results in cartilage repair activity in an experimental canine model of OA, which corroborates with the structural observations of cartilage repair by surrogate markers in humans (Wiegant et al, 2014). Despite these promising results little is known about the exact mechanisms that boost them. Objectives: This study evaluates for the first time the regenerative transcriptional response during joint distraction in an experimental model of osteoarthritis. Methods: Knee OA was induced in 8 dogs according to the groove model. Ten weeks after OA induction, 4 dogs received joint distraction (D) and 4 dogs served as disease controls (OA). After 4 weeks of distraction the animals were sacrificed and knee tissues including fat pad, synovium, meniscus, bone and cartilage were harvested. qPCR analysis of more than 35 state-of -the-art regenerative gene markers was performed. Results: The OA group revealed an upregulation of typical OA markers, like matrix metalloproteinases, collagen, and apoptosis markers confirming the OA disease cascade in specifically cartilage, bone and synovial tissue. Joint distraction caused downregulation of the typical OA markers and the maintenance of some important matrix remodeling genes for regeneration, e.g. aggrecanase. Moreover, genes from several pathways were differentially expressed between the D and OA group, including TGF-β, Wnt, and Notch signaling pathways. Interestingly, a high number of events occurred in bone, highlighting the importance of this tissue in the regenerative outcome of joint distraction on OA cartilage. Conclusions: Distraction is a good candidate for knee OA treatment resulting in prolonged clinical and structural changes. This study demonstrates distinctively that joint distraction initiates a transcriptional regulation of several important regenerative genes indicating that a reset of joint homeostasis can lead to cartilage repair in OA. References: Sustained clinical and structural benefit after joint distraction in the treatment of severe knee osteoarthritis. Wiegant K, van Roermund PM, Intema F, Cotofana S, Eckstein F, Mastbergen SC, Lafeber FP. Osteoarthritis Cartilage. 2013 Nov;21(11):1660-7. Evidence for cartilage repair by joint distraction in a canine model of osteoarthritis. Wiegant K, Intema F, van Roermund PM, Barten-van Rijbroek AD, Doornebal A, Hazewinkel HA, Lafeber FP, Mastbergen SC. Arthritis Rheumatol. 2014 Oct 9. [Epub ahead of print] Acknowledgements: Supported by a grant from the Dutch Arthritis Foundation Disclosure of Interest: None declared